Poorer self-reported mental health and general health among first year upper secondary school students do not predict school dropout: a five-year prospective study - Goll, Charlotte Bjørnskov; Sørlie, Tore; Friborg, Oddgeir; Ottosen, Karl Ottar; Sæle, Rannveig Grøm (Frontiers in Psychology, 2024)
Education is important for socioeconomic, work and health status; thus, dropping out of secondary school is of major concern. In Norway, 1 out of 5 is dropping out from upper secondary education. Academic performance is a known predictor for dropout, but the role of mental and general health status is studied less. By use of student data collected during the first school year we examined the accumulated risk of school dropout over five years.Students entering upper secondary school in a North-Norwegian region (Troms County) completed a comprehensive questionnaire during August 2010 (N=1676, 69% response rate). The contribution of mental and general health problems in predicting five-year dropout was of primary interest, adjusted for demographics and academic performance.One-third of the students had dropped out after five years. A logistic regression analysis showed no significant effect of mental and general health problems on dropout. Among the covariates, higher grades from lower secondary education reduced the chance of dropping out (OR = .31; p < .001). Subgroup analyses showed that students in the vocational track reported poorer mental and general health, compared to students in the general track, but this difference was not related to dropout. General track students were also less likely to drop out than vocational track students (OR for dropout .66; p < .05). In conclusion, lower grades from lower secondary education represented a warning flag for school dropout during upper secondary education whereas mental health issues were not.